Pentingnya Pendidikan Moral Sejak Anak Sekolah Dasar - Heru Siswanto (Darajat: Jurnal Pendidikan Agama Islam, 2018)
People said that education is development. It creates choices and opportunities for people, reduces the twin burdens of poverty and diseases, and gives a stronger voice in society. For nations it creates a dynamic workforce and well-informed citizens able to compete and cooperate globally - opening doors to economic and social prosperity. However, the main purpose of education is not only to create skillful and bright brain individual, but also a moral citizen. Moral education is becoming an increasingly popular topic in education. Media reports of increased violent juvenile crime, sexual harassment, corruption, illegal logging, and other violence-one of them taken place at one of the "elite" university of our countryhave caused many to declare a moral crisis in our nation, and the demanding reflection on our philosophy and practice of education. While not all of these social concerns are moral in nature, and most have complex origins, there is a growing trend towards linking the solutions to these and related social problems to the teaching of moral and social values in our public schools, in elementary and higher level. Moral education becoming.